Effect of tillage and irrigation on soil-water-plant relationship and productivity of winter maize (Zea mays) in north Bihar - KUMAR, SANJEEV; SHIVANI, SHIVANI; MISHRA, S; SINGH, V P (The Indian Journal of Agricultural Sciences, 2011)
Field experiments were conducted for 2 consecutive years from 2002-04 in winter (rabi) season at the University, Pusa, Samastipur, Bihar comprising 16 treatment combinations of tillage and irrigation. The physical properties of the soil of rotavator tilled plots were found significantly superior over all other tillage practices in respect of bulk density (1.33 and 1.30 mgi m3), soil strength (2.10 and 2.05 MPa), infiltration rate (0.420 and 0.432 cm/ha) and porosity (49.81 and 50.94%) during both the years respectively. Plant height (1 89.33 and 190.07 cm), leaf area index (2.673 and 2.728), dry matter accumulation/plant (369.77 and 392.78 g) and relative leafwater content (94.61% and 93.36%) of rotavator tilled maize were significantly higher over zero-tillage in 2002-03 and 2003-04 respectively. Crop receiving 5 or 6 irrigation showed significant superiority in respect of yield and yield attributing characters over crop receiving 3 and 4 irrigation. Rotavator tilled maize showed significant higher water expense efficiency (107.4 and I14.6lkgiha-cm) over all other tillage practices while it was found minimum (82.50 and 90.74 kgiha-cm) with 6 irrigations and maximum (88.44 and 97.56 kg/ha-cm) with 3 irrigations during 2002-03 and 2003-04 respectively. Rotavator tilled maize fetched maximum grain yield (5 83 1 and 5 960 kg/ ha) and maximum net return (Rs 16 173 and Rs17 493) with 5 to 6 irrigations during 2002-03 and 2003-04 respectively.